Physicians’ knowledge on obstructive sleep apnea. How are we after five years? - Rosales, Edmundo (2007)
Objective: To determine physicians’ knowledge level on obstructive sleep apnea and to compare it with a report published in 2001. Design: Cross-sectional study. Setting: Five congresses developed during 2006. Participants: Congress assitants. Interventions: Questionnaire with 18 questions about knowledge of the syndrome. This questionnaire was self administered, unique and anonymous. Main outcome measures: Knowledge of the syndrome, its diagnosis and treatment. Results: Two hundred and forty-one questionnaires were successfully obtained. The age of the participants was 36,1±11,7 [20 to 76] years. Two hundred and thirty seven (98%) knew the meaning of ‘sleep apnea’, acquired in pre-degree studies in 39%; 16% identified disorders associated to the syndrome; 149 (62%) affirmed it appeared exclusively in obese men and 45 (19%) that it was most frequent in premenopausal women; 107 (45%) did not know the prevalence of snore in 35 year-old men or older, 184 (76%) affirmed that hypersomnia was the most frequent symptom and 94 (39%) that insomnia was described by patients with this syndrome. One hundred and eight (45%) did not investigate by symptoms related to the syndrome in their daily medical practice; 70 (29%) did not recognize polysomnography or respiratory polygraphy as a diagnosis method; 147 (61%) identified treatment modalities but nobody identified all of them; 89 (37%) did not know that there were specialists who study this syndrome in Peru. Conclusions: Physicians know more about this disease in comparison with the report done 5 years ago; nevertheless, this knowledge is still deficient. The inclusion of this subject in the education of physicians and other health professionals should be promoted.